1975
DOI: 10.3109/10520297509117045
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy of Tissue Prepared for Scanning Electron Microscopy by Ethanol-Cryofracturing

Abstract: Tissue processed for scanning electron microscopy by ethanol-cryofracturing combined with critical point drying was embedded and sectioned for transmission electron microscopy. Study of specimens cut in a plane passing through the fracture edge indicated that preservation of cellular fine structure of fractured cells was excellent. Even at the most peripheral edge of the fracture there was no evidence that movement of cytoplasmic components occurred to distort the original structural organization of fractured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Investigators interested in the deep structure of cartilage have used cutting, tearing (breaking wet cartilage), and resin cracking techniques (Takata, 1974) to expose deep structures for SEM examination. Cryofracture after dehydration is superior to other techniques (Clark, 1985;Humphreys et al, 1975). Cryofractures tend to follow planes between the collagen fibers, or, because the frozen fibrils are brittle, break through them with minimal distortion.…”
Section: Considerations In the Preparation Of Cartilage For Semmentioning
confidence: 99%
“…Investigators interested in the deep structure of cartilage have used cutting, tearing (breaking wet cartilage), and resin cracking techniques (Takata, 1974) to expose deep structures for SEM examination. Cryofracture after dehydration is superior to other techniques (Clark, 1985;Humphreys et al, 1975). Cryofractures tend to follow planes between the collagen fibers, or, because the frozen fibrils are brittle, break through them with minimal distortion.…”
Section: Considerations In the Preparation Of Cartilage For Semmentioning
confidence: 99%
“…In order to facilitate deep-etching, ethanol has been used in combination with freeze-drying or critical point drying for scanning electron microscopy (Boyde & Wood, 1969;Humphreys et al, 1974Humphreys et al, ,1975. Recently Schiller & Taugner (1980) have shown that fractured tissues can be deep-etched and replicated after prolonged soaking in ethanol.…”
Section: P E N E T R a T I N G C R Y O P R O T E C T A N T Smentioning
confidence: 99%
“…Following this fixation, the tissues were dehydrated in increasing concentrations of ethanol/H,O (30%, 50%, 75%, 90%, and 100%). Each fixed and dehydrated tissue strip was frozen quickly in liquid nitrogen and then fractured manually with a razor blade into two roughly equal longitudinal halves to expose the internal matrix architecture, using a technique similar to that of Hump h r e y s a n d colleagues (20). T h e f r a c t u r e d rectangular strips of tissue were then critical point dried, aligned vertically, mounted, and sprayed with gold-palladium.…”
Section: Methodsmentioning
confidence: 99%